In-vitro fractional flow reserve of coronary artery - Qamaruz Zaman Ali (2019)
The current standard method of determining the amount of stenosis across coronary artery are invasive, risky and even costly. This project aims to firstly, study the possibility of using an external in-vitro test setup to simulate human hemodynamics. Secondly, to take pressure and flow rate measurements. The project involves testing of 3D printed coronary artery adapted from an actual human body and integrate it into the in-vitro test setup. The main objective of this project is to be able to obtain the pressure as well as the flow rate waveforms of the 3D printed coronary artery by performing catheterization process. Using the data obtained, Fractional Flow Reserve can be computed to analyze the amount of stenosis present. In addition, it is essential to achieve a free-leakage test setup so as to accurately replicate the cardiovascular system of the left side of the heart. A number of modification and iteration processes were made to the existing in-vitro setup to eliminate leakages. The results obtained from the experiment prove that the in-vitro setup is reliable and accurate in taking measurements data and that catheterization process is possible to be carried out. Overall, the experiment met all the objectives and proved to be a successful one. Future project can include improvement in the test rig design in order to eliminate leakage issues. The design can be made to increase efficiency in conducting the experiment. To aid further understanding using different 3D printed coronary artery specimens would better show the advantages and disadvantages of non-invasive methods such as the in-vitro.